Romania : Third Review Under the Stand-By Arrangement-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report ;, 2012)
This paper discusses key findings of the Third Review of Romania's economic performance under a program supported by a 24-month Stand-By Arrangement (SBA). The authorities are on track to achieve their 2011-12 deficit targets, but stepped-up efforts are needed on key structural reforms. Inflation has dropped sharply, reflecting food prices deflation and the removal of the VAT base effect. All end-September quantitative performance criteria and indicative targets were met, and inflation returned to the inner band of the inflation consultation mechanism.